Sound environment of Cities - Hassan, Susan Abd (Iraqi Journal of Architecture and Planning, 2018)
The sound environment in the Traditional Baghdad city specified with sound elements and relationships between sounds that define human sound environment, and had the greatest impact where natural sounds as human voice, animal and natural sound in addition to the voices of the traditional industries and the old means of transportation. The Recent changes in the traditional urban fabric that accompanied with the requirements of contemporary life. Of transportation, machinery and various industries affected in the structure of the traditional Baghdad urban fabric and Incision straight roads to the movement of vehicles and concentration height buildings on both sides of these roads, with the changing pattern of use of residential to commercial, affected on the sound environmental and on perceptional preference for the traditional city .For this reason, An analytical methods and questionnaire studies were conducted in several areas in Al-Kadhimiya city as an example of the traditional cities. The areas included a wide range of sound types and different sound level, from highly traffic-noise in Akkad Street to quiet Al-zuqaq (traditional street).Consistent relationships were found between measured overall sound levels and perceived sound quality, however, sound source identification was found to be a stronger predictor of sound quality than measured sound levels. Sound quality was negatively related to presence of technological sounds (e.g., road-traffic noise, gasoline generators) in modern type of City Street and positively related to presence of nature sounds in traditional street.